Preoperative Oral Carbohydrate Levels in Patients with Type 2 Diabetes Mellitus: The Clinical Guiding Significance of Free Fatty Acids - Yang, Jiuhui; Ding, Xiangming; Wang, Ning; Pan, Yujin; Xiao, Erwei; Mu, Senmao; Wang, Liancai; Li, Dongxiao; Li, Deyu (Frontiers in Surgery, 2022)
Background: It is still controversial whether preoperative oral carbohydrate (POC) should be applied to patients with type 2 diabetes mellitus (T2DM) in the enhanced recovery after surgery (ERAS) protocol. There is no relevant consensus or indicators to guide T2DM patients to take POC. Methods: Totally 164 T2DM patients who underwent laparoscopic hepatectomy were analyzed. According to the level of blood free fatty acids (FFAs) and whether to receive POC, the patients were divided into 6 groups, which included low FFAs carbohydrate group (LFFAC group), low FFAs fasting water group (LFFAF group), medium FFAs carbohydrate group (MFFAC group), medium FFAs fasting water group (MFFAF group), high FFAs carbohydrate group (HFFAC group) and high FFAs fasting water group (HFFAF group). Results: Patients with low FFAs level showed a better perioperative blood glucose control and a lower incidence of postoperative complication compared with that in medium and high FFAs group, especially when patients received POC. Further analyses revealed that the postoperative plasma concentrations of IL-6 and TNF-α were significantly decreased in POC group compared with fasting water group, except for patients with high FFAs level. Receiver operating characteristic (ROC) curve analysis revealed that when the FFAs concentration is higher than 0.745 mmol/L, the risk of poor blood glucose control during perioperative period was increased. Conclusions: FFAs have clinical guiding significance for the application of POC in patients with T2DM under ERAS adminstation. T2DM patients with low FFAs are more suitable for receiving POC.